2021
DOI: 10.1002/adma.202106520
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Polymer‐Coated CaCO3 Reinforces Radiotherapy by Reprogramming the Immunosuppressive Metabolic Microenvironment

Abstract: Radiotherapy is widely exploited for the treatment of a large range of cancers in clinic, but its therapeutic effectiveness is seriously crippled by the tumor immunosuppression, mainly driven by the altered metabolism of cancer cells. Here, a pH‐responsive nanomedicine is prepared by coating calcium carbonate (CaCO3) nanoparticles with 4‐phenylimidazole (4PI), an inhibitor against indoleamine 2,3‐dioxygenase 1 (IDO‐1), together with zinc ions via the coordination reaction, aiming at reinforcing the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 53 publications
1
48
0
Order By: Relevance
“…We then found that CT26 cells under acidic incubation (e.g., pH 6.5) showed increased resistance to external X-ray irradiation in comparison with those under the normal incubation (e.g., pH 7.4) (Figure C), which is consistent with previous studies . However, we found that the addition of fCaCO 3 -PEG (1.2 mM) to these CT26 cells under acidic incubation would increase their response to X-ray irradiation, indicating PFCE@fCaCO 3 -PEG could efficiently reverse tumor-acidity-induced radiotherapeutic resistance.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We then found that CT26 cells under acidic incubation (e.g., pH 6.5) showed increased resistance to external X-ray irradiation in comparison with those under the normal incubation (e.g., pH 7.4) (Figure C), which is consistent with previous studies . However, we found that the addition of fCaCO 3 -PEG (1.2 mM) to these CT26 cells under acidic incubation would increase their response to X-ray irradiation, indicating PFCE@fCaCO 3 -PEG could efficiently reverse tumor-acidity-induced radiotherapeutic resistance.…”
Section: Resultssupporting
confidence: 91%
“…Radiotherapy (RT) is currently a widely used cancer treatment modality in clinics. , As a type of oxygen-consuming cancer treatment, the therapeutic efficacy of RT has been shown to be obviously restricted by limited intratumoral oxygen contents as that would limit the production of cytotoxic reactive oxygen species (ROSs), by which RT kills cancer cells. , Additionally, tumor acidity has also been confirmed to be a limiting factor for effective RT treatment by impairing the lifetime of these RT-generated ROSs. , With the advance of functional nanomaterials, we have witnessed the successful fabrication and utilization of diverse perfluorocarbon (PFC)-based oxygen nanoshuttles to potentiate RT treatment and other cancer treatments by utilizing their efficient oxygen-loading capacity. Furthermore, some pioneering studies have elucidated that efficient tumor hypoxia attenuation or tumor acidity neutralization could also improve the abscopal effect of RT by reversing tumor immunosuppression to more efficiently reject metastatic tumors. However, the impact of tumor glucose metabolism modulation on the therapeutic potency of RT has been relatively less studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the inherent non-toxic and biocompatibility of Ca-NMs facilitate their applications in tumor diagnosis and treatment [ 30 ]. Therefore, Ca-NMs, such as calcium phosphate (CaP) [ 31 ], calcium carbonate (CaCO 3 ) [ 32 34 ], and hydroxyapatite (HAp) [ 35 , 36 ], are an attractive class of inorganic calcium-based materials because of their degradation products native presence in the human environment. In addition, calcium peroxide (CaO 2 ) is also included in this functional calcium-based material due to its powerful anti-tumor properties.…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al revealed that T cells could promote ferroptosis in tumor cells, thus providing a potential therapeutic approach 11 . Feng et al reported that reprogramming the immunosuppressive metabolic microenvironment could improve the curative effect of radiotherapy in breast cancer 50 . In this study, the functional enrichment analysis and KEGG pathway analysis revealed that immune cells and immune-related pathways were highly enriched in glioma-related biological processes.…”
Section: Discussionmentioning
confidence: 99%